Theoretical Calculation of Heat and Material Balance for Oil Sludge Pyrolysis Process by Solid Heat Carrier Method - Zhengyang Zhang; Yue Ma; Fengzhi Guo; Changtao Yue (Energies)
In this study, oil sludge from Jilin Petrochemical of China was selected to carry out the Fischer assay and proximate analysis. According to the properties of the Jilin oil sludge and its pyrolysates, the material and heat balance of the pyrolysis process was deduced theoretically based on 1000 kg of received base oil sludge. The results show that the solid heat carrier method can be used in the pyrolysis of oil sludge, and a new process flow is proposed. According to the heat required and heat provided in the rotary reactor and in the fluidized bed, 5940 kg of ash was needed as a solid heat carrier, and 25 kg of liquefied petroleum gas was needed as a supplementary fuel besides the semi-coke and retorting gas. The total input heat and output heat were 13.65 GJ and 10.04 GJ. The loss was 3.61 GJ and the thermal efficiency was 73.6%.